The Rice SPOTTED LEAF4 (SPL4) Encodes a Plant Spastin That Inhibits ROS Accumulation in Leaf Development and Functions in Leaf Senescence - Song, Giha; Kwon, Choon-Tak; Kim, Suk-Hwan; Shim, Yejin; Lim, Chaemyeong; Koh, Hee-Jong; An, Gynheung; Kang, Kiyoon; Paek, Nam-Chon (Frontiers in Plant Science, 2019)
Lesion mimic mutants (LMMs) are usually controlled by single recessive mutations that cause the formation of necrotic lesions without pathogen invasion. These genetic defects are useful to reveal the regulatory mechanisms of defense-related programmed cell death in plants. Molecular evidence has been suggested that some of LMMs are closely associated with the regulation of leaf senescence in rice (Oryza sativa). Here, we characterized the mutation underlying spotted leaf4 (spl4), which results in lesion formation and also affects leaf senescence in rice. Map-based cloning revealed that the γ ray-induced spl4-1 mutant has a single base substitution in the splicing site of the SPL4 locus, resulting in a 13-bp deletion within the encoded microtubule-interacting-and-transport (MIT) spastin protein containing an AAA-type ATPase domain. The T-DNA insertion spl4-2 mutant exhibited spontaneous lesions similar to those of the spl4-1 mutant, confirming that SPL4 is responsible for the LMM phenotype. In addition, both spl4 mutants exhibited delayed leaf yellowing during dark-induced or natural senescence. Western blot analysis of spl4 mutant leaves suggested possible roles for SPL4 in the degradation of photosynthetic proteins. Punctate signals of SPL4-fused fluorescent proteins were detected in the cytoplasm, similar to the cellular localization of animal spastin. Based on these findings, we propose that SPL4 is a plant spastin that is involved in multiple aspects of leaf development, including senescence.